SYSTEMIC THINKING MEANS - Juli Iswanto (Journal Analytica Islamica, 2021)
Thinking right requires means or tools of thinking. Thismeans is certain, so scientific activity will not be maximized withoutthe means of scientific thinking. For a scientist, mastery of the meansof thinking is a must, because without mastery of scientific means, hewill not be able to carry out good scientific activities. The method usedto obtain the data needed in this discussion is the Library Researchmethod. The result is that language is a means of communicatingsystematic ways of thinking in acquiring knowledge. Withoutlanguage skills, a person will not be able to carry out scientificactivities systematically and correctly. While logic helps humans tothink systematically which can be justified. If you want to do thinkingactivities correctly, you must use logical thinking rules. The statisticsshould not be underestimated by people who want to be able to carryout scientific activities well. Mastery of statistics is indispensable forpeople who will draw valid conclusions. Statistics must be seen asparallel to mathematics